The IPCC Made Three Fatal Errors in Assumptions about CO2 - H. Douglas Lightfoot (Journal of Basic & Applied Sciences, 2020)
In 2013, and following from 1990, the Intergovernmental Panel on Climate Change (IPCC) issued Climate Change 2013:The Physical Science Basis (AR5) claiming the concentration of CO2, air temperature, and water vapor go up and down together; the air can hold more water vapor and the increased warming by water vapor adds to the warming by CO2. Pictorially: CO2↑, T↑, WV↑. Although no scientific evidence is offered, this concept has become widely accepted because of the fear that CO2 might increase the Earth’s temperature to dangerous levels. In developing research to evaluate the IPCC claims, it is noted that the temperature at the Equator is always higher than that in the Arctic and Antarctic. The Gas Law of Charles/Gay-Lussac states that at constant pressure the volume of a gas is inversely proportional to the absolute temperature. Thus by applying this law, the CO2 concentration is always higher at the Poles than at the Equator. Thus, when moving from the Poles to the Equator, temperature goes up, CO2 goes down and water vapor goes up. Pictorially: T↑, WV↑, CO2↓. The warming effects of CO2 and water vapor do not add; they oppose each other. This is a robust conclusion based on hard numbers. It is opposite to the claim by the IPCC and proves there are errors in the assumptions.